ORALITY, SYMBOLISM AND MYTHICAL ANDEAN WORLD IN “OROVILCA” - Viera, Sara (2013)
In this article we will examine the discursive function of the story “Orovilca”. Our hypothesis suggests that the mythical and symbolic element of the Andean cosmovision is the basis on which the narrative substrate is built up, as well as the mechanism on which the two main characters, Salcedo and Wilster, are created. From our point of view, both characters have features that link them with the bird and the serpent, an aspect, which although pointed out by Alejandro Ortiz Rescaniere and Gladys Marin, has not been clearly proved yet. What we propose is to analyze the significance of both characters because it is really on them that the narrative tension is based and articulated, as well as on the spaces in which the whole story unfolds.